A Study on The Deep (Meaningful) Learning Perceptions of The Teacher Candıdates in The Philosophy of Education Course Carried Out With Distance Education - Koca, Bülent Uğur; Tatlı, Cemal (My University, 2022)
In this study, it was aimed to determine the deep (meaningful) learning perception levels of teacher candidates in the philosophy of education course conducted with blended learning. Within the framework of this purpose, learning and teaching activities were carried out in a learning environment developed based on the flipped learning method. In the study, the deep learning perception levels of teacher candidates were examined in terms of various variables. The research, which was carried out with a quasi-experimental design, was carried out on three groups: Mathematics and Science Education, Turkish and Social Sciences Education, and Elementary Education. 42 (%33.33) teacher candidates from the Mathematics and Science Education department, 40 (%31.74) teacher candidates from the Turkish and Social Sciences Education department, and 44 (%34.92) teacher candidates from the Elementary Education department participated in the research. “Deep (Meaningful) Learning Perception Scale” developed by Tatli (2022) was used to obtain research data. As a result of the research, it has been determined that there is no significant difference between the deep learning perception levels of teacher candidates and their gender, department, theoretical and applied course preferences, technologies used in internet access and learning resources. In the study, it was concluded that the deep learning perception levels of the teacher candidates in the study groups were high and close to each other. Ethics Committee Report of the Research; It has been taken from the Scientific Research and Publication Ethics Committee of Mus Alparslan University, with the meeting number 07 and decision 59, dated 11.05.2022.